PSALM BY THE RIVERS OF BABYLON AS PART OF SIGISMUND TODUŢĂ'S CHORAL OUTPUT - IONAȘCU, Stelian (Studia Universitatis Babes-Bolyai Musica, 2009)
The first choral setting of Psalm 136 belongs to Gavriil Musicescu. To be more precise, By the Rivers of Babylon concerto bears an explanatory note, as follows “from the repertoire of the choir in Ismail, Basarabia” - the composer's birthplace; Musicescu had in 1858 – 1872, a profound professional relationship with this choir, which means that this setting is not an original work.